(untitled) (Hasanuddin Civil and Bussiness Law Review, 2024)
Economic Rights as one of the exclusive rights for creators is a form of intellectual property protection for creators to obtain economic benefits from creations. Song creators are entitled to economic rights over their creations. This is in accordance with the principle of sustainability of a work or the incentive theory which prioritizes the sustainability of a creation. The sustainable principle of a work aims to ensure that the creator can continue to realize his ideas and create new works. A work in the form of a work of song and/or music has economic rights for Commercial Use in the form of Royalties, namely compensation for the use of the economic rights of a Work received by the Creator. The National Collective Management Organisation (LMKN) is an institution authorized by law to collect and collect song royalties for the commercial use of songs and/or music. However, the provisions of Article 87 of Undang-Undang No. 28 of 2024 concerning of Copyright (UUHC) regulates that to obtain economic rights and royalties, the creator must be a member of the Collective Management Institution. Creators who are not members of an LMK do not receive royalties that have been collected by the LMKN. These administrative regulations require the creator of songs or music to be a member of an CMO. In fact, one of the aims of protecting economic rights is to increase income and support the welfare of songwriters. Non-CMO song creators who do not receive royalties, their economic rights to their creations are not fulfilled